Eve and the Others: Nogarola' s Proto-feminist Legitimization of Subversive Women's Voices - Gabrielli, Francesca Maria (2008)
The humanist scholar Isotta Nogarola (1418-1466) devoted herself to the pursuit of knowledge without marrying or entering a convent: she secluded herself in a room of her mother’ s house and chose a life of celibacy. This unprecedented and carefully pondered decision enabled her to fulfill an urgently felt intellectual vocation, without overtly defying the patriarchal horizon of expectation. Nogarola’ s existential choice, accepted by her contemporaries as religious rather than intellectual, can be interpreted as an astute negotiation between androcentric impositions and the individual needs of a woman. The author’ s contribution to the Renaissance discourse on gender is born out of a similar need to disguise complex gender issues under a patriarchally acceptable mask. Nogarola accepts and thematizes in her work the stereotype of female inferiority. On the other side, her opus - instead of offering naive claims of women’ s superiority, which simply invert the terms of the hierarchical binary opposition male/female - is interwoven with allusions to the equality and interchangeability between male and female figures, which successfully bypass traditional gender dichotomies. This paper aims to study Nogarola’ s subversive representation of female figures, whose subtly proto-feminist legitimization serves as a means of self-authorization, focusing primarily on the utterly sophisticated defense of Eve.
Projekt MZOS
ENG